Impact of Boric Acid on Photocatalytic Oxidation - T.Muhammad Ashari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Greywater reuse is considered as one solution in solving water scarcity problem in the world because it is less contagious and less polluting to environment than the entire municipal wastewater. Greywater is easier to treat and reuse it. One possibility to treat greywater is using constructed wetland followed by an advanced oxidation process such as photocatalytic oxidation. This process removes organic materials in waste water by oxidation via hydroxyl radicals. There was discussion about the effects of the solution inorganic matrix such as borate on the photocatalytic oxidation. Borate a common constituent of greywater was reported to inhibit photocatalytic oxidation. This research tried to determine the effect of boric acid on photocatalytic oxidation spiked with boric acid in concentration of 5 to 200 mg/L using aqueous TetraEGDME solutions. It was found that there is no inhibition of photocatalytic oxidation process when boric acid is present and pH is acidic (about 4-5).